ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN MEKANISME CORPORATE GOVERNANCE TERHADAP KUALITAS LABA DAN NILAI PERUSAHAAN - Paramitha Anggia Puteri; Abdul Rohman (Diponegoro Journal of Accounting, 2012)
The objective of this research is to examine the influence of Investment Opportunity Set (IOS) and corporate governance mechanism (the number of audit committee meetings, independence of commissioner, institutional ownership, and managerial ownership) toward earnings quality and firm value. This research also examined the influence of earnings quality to firm value. This research used samples from manufacturing companies that listed on Indonesia Stock Exchange (IDX) during 2006-2010. Based on purposive sampling technique, it got 24 companies as research samples, so as long as 5 years observation there were 120 annual reports were analyzed. The method of analysis of this research was multiple regression. The results of this research showed that earnings quality doesn’t have significant influence to firm value; Investment Opportunity Set (IOS) has significant influence to earnings quality and firm value; the number of audit committee meetings has significant influence to earnings quality but it doesn’t have significant influence to firm value; independence of commissioner doesn’t have significant influence to earnings quality but it has significant influence to firm value; institutional ownership has significant influence to earnings quality and firm value; meanwhile managerial ownership doesn’t have significant influence to earnings quality but it has significant influence to firm value.